Pemanfaatan Instant Messenger Telegram Sebagai Alat Penyebaran Paham Radikal Di Indonesia - Alfhatheh Mohammad (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study is to find out the use of instant messenger Telegram as a tool for spreading radicalism in Indonesia. Defined as a research method based on post-positivism philosophy (correcting weaknesses, that reality is real, and researchers cannot get the truth from reality if researchers are not directly involved), used to examine the condition of natural objects, where researchers are as key instruments, data collection techniques are carried out by in-depth interviews, then to test the validity of the researchers using triangulation (combined), data analysis is inductive / qualitative. The results of the Qualitative Method research show that true instant messenger Telegram is used by many radical groups in communicating and for the purpose of expanding the network of radicalism. So that the Telegram should have a team or technology that can filter radical content directly, so that these groups cannot easily launch their actions by spreading propaganda or the ideologies of their groups.